2018
DOI: 10.3390/buildings8050067
|View full text |Cite
|
Sign up to set email alerts
|

Design Lessons from Three Australian Dementia Support Facilities

Abstract: There is a significant increase in the number of people with dementia, and the demand for residential support facilities is expected to increase. Providing an appropriate living environment for residents with dementia, which can cater for their specific needs is crucial. Residential aged care design can impact the quality of life and wellbeing of the residents. In this investigation, three recently constructed dementia support facilities in Victoria, Australia are selected for evaluation. Through fieldwork obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 16 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…These methods have been devised to make people with dementia more easily aware of their environment. It is important for people with dementia, including Alzheimer's type dementia, to live in a supportive and therapeutic environment (Calkins, ; Chau et al, ). The World Health Organization′s () International Classification of Functioning states that mutual interaction between humans and their environment is important and it presents the importance of social models to improve the environment to overcome disorders that reduce life functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods have been devised to make people with dementia more easily aware of their environment. It is important for people with dementia, including Alzheimer's type dementia, to live in a supportive and therapeutic environment (Calkins, ; Chau et al, ). The World Health Organization′s () International Classification of Functioning states that mutual interaction between humans and their environment is important and it presents the importance of social models to improve the environment to overcome disorders that reduce life functions.…”
Section: Discussionmentioning
confidence: 99%
“…These methods have been devised to make people with dementia more easily aware of their environment. It is important for people with dementia, including Alzheimer's type dementia, to live in a supportive and therapeutic environment (Calkins, 2018;Chau et al, 2018). The World Health…”
Section: Discussionmentioning
confidence: 99%
“…The paper by Hing-wah Chau, Clare Newton, Catherine Mei Min Woo, Nan Ma, Jiayi Wang and Lu Aye [10] focused on the specific group of people with dementia. This paper investigated three recently constructed dementia support facilities in Victoria, using fieldwork observation, design evaluation and space syntax analysis.…”
Section: Healthcare Environmentsmentioning
confidence: 99%
“…Based on self-reports of 267 participants in a survey, Tauber (2012) [69] concluded that connection to nature directly affects an individual's physical wellbeing and psychological wellbeing. Connection to nature may also be considered to be a positive stimuli to promote engagement and pleasure for people with dementia [70]. Many researchers [51,52,[58][59][60][61][62][71][72][73][74] have argued for the wellbeing benefits of connection to nature.…”
Section: Connection To Nature As a Resourcementioning
confidence: 99%